Sirtuin 3 Plays a Critical Role in the Antidepressant- and Anxiolytic-like Effects of Kaempferol - Hao-Yuan Li; Jing Wang; Ling-Feng Liang; Shi-Yu Shen; Wei Li; Xiao-Rong Chen; Bing Li; Yu-Qiu Zhang; Jin Yu (MDPI AG, 2022)
An estimated 20% of women experience depression at some point during menopause. Hormone replacement therapy (HRT), as the main therapy for depression and other menopausal syndromes, comes with a few undesirable side effects and a potential increase in cancer and cardiovascular risk. Consequently, there is a dire need for the development of new therapies to treat menopausal depression. Oxidative stress combined with the decline in sex hormones might explain the occurrence of psychological symptoms characteristic of menopause. Therefore, antioxidants have been suggested as a promising therapy for aging-associated diseases, such as menopausal depression. As a flavonoid antioxidant, kaempferol might have a potential neuroprotective action. Hence, the study was conducted to assess the potential antidepressant action of kaempferol and clarify the underlying mechanism. The results show that kaempferol has potential beneficial effects on VCD-induced rodent model of menopausal depression and produces antioxidant effects as well as increases the deacetylation of superoxide dismutase 2 (SOD2) and the protein level of Sirtuin3 (Sirt3) in the hippocampus. On the contrary, Sirt3 depletion abrogated the antidepressant- and anxiolytic-like effects as well as antioxidant effects of kaempferol. In conclusion, kaempferol might produce antidepressant effects via upregulating the expression of Sirt3, the major deacetylase in mitochondria, and subsequently activate the mitochondrial antioxidases. These findings shed some light on the use of kaempferol or vegetables and herbs that contain kaempferol as a complementary therapy for menopausal depression.